Influência de parâmetros da semeadura mecanizada no estabelecimento inicial do milho em terras baixas - (:unkn) unknown (Universidade Federal do Pampa, 2025)
Technological advances in recent decades, such as improvements in spatial arrangement, notillage systems, and efficient use of machinery, have significantly contributed to increased productivity. Among agricultural operations, sowing stands out as one of the key factors determining crop success, especially due to its influence on emergence, plant stand, and early plant development. However, variables such as sowing speed, downforce, and prior management of soil cover may compromise sowing quality, particularly in rainfed systems on lowland soils, which are common in the Western Frontier of Rio Grande do Sul. In this region, crop–livestock integration and rotation with irrigated rice increase the importance of studies on crop establishment under low soil cover conditions in lowland areas. In this context, the objective of this study was to evaluate the initial growth of maize under different soil cover management systems, downforce levels applied to the seeding row, and sowing speeds. The experiment was carried out in Alegrete, RS, using a three-factor (3×2×3) experimental design composed of three soil cover management systems (conventional, grazed, and notillage), two downforce levels (598 and 853 N), and three sowing speeds (3.5, 6.0, and 9.0 km h−1). Variables related to emergence and early corn development were evaluated, including emergence speed index (ESI), plant distribution, seed placement depth, initial plant stand, stem diameter, plant height, and shoot dry mass. The results showed that soil cover management was the most influential factor, significantly affecting ESI, stem diameter, plant height, and shoot dry mass production. The no-tillage system presented the best performance, standing out for higher moisture retention and lower soil temperature variation—key factors for early vigor under rainfed conditions. Sowing speed also had a relevant impact: higher speeds reduced seed placement depth and increased irregularities in plant spacing. Downforce, although important, showed a limited effect on most variables, interacting significantly only in specific cases. Overall, the combination of lower sowing speeds, higher downforce, and no-tillage soil cover management provided the best conditions for the initial establishment of corn in lowland soils, highlighting the need for precise adjustments in sowing operations to maximize yield potential in rainfed systems. Keywords: Corn seeding; Down force; Operating speed, Soil cover management; Lowland soils.
Keywords: Engenharia agrícola; Trigo; Semeadura; Down force; Terras baixas; Agricultural engineering; Wheat; Lowland soils; CIENCIAS AGRARIAS